Women with Premenstrual Dysphoria Lack the Seemingly Normal Premenstrual Right-Sided Relative Dominance of 5-HTP-Derived Serotonergic Activity in the Dorsolateral Prefrontal Cortices - A Possible Cause of Disabling Mood Symptoms - Eriksson, Olle; Wall, Anders; Olsson, Ulf; Marteinsdottir, Ina; Holstad, Maria; Ågren, Hans; Hartvig, Per; Långström, Bengt; Naessén, Tord (PLOS ONE, 2016)
Study Objective To investigate potential quantitative and qualitative differences in brain serotonergic activity between women with Premenstrual Dysphoria (PMD) and asymptomatic controls. Background Serotonin-augmenting drugs alleviate premenstrual mood symptoms in the majority of women with PMD while serotonin-depleting diets worsen PMD symptoms, both indicating intrinsic differences in brain serotonergic activity in women with PMD compared to asymptomatic women. Methods Positron-emission tomography with the immediate precursor of serotonin, 5-hydroxytryptophan (5-HTP), radiolabelled by 11C in the beta-3 position, was performed in the follicular and luteal phases for 12 women with PMD and 8 control women. Brain radioactivity–a proxy for serotonin precursor uptake and synthesis–was measured in 9 regions of interest (ROIs): the right and left sides of the medial prefrontal cortex, dorsolateral prefrontal cortex, putamen and caudate nucleus, and the single “whole brain”. Results There were no significant quantitative differences in brain 5-HTP-derived activity between the groups in either of the menstrual phases for any of the 9 ROIs. However, multivariate analysis revealed a significant quantitative and qualitative difference between the groups. Asymptomatic control women showed a premenstrual right sided relative increase in dorsolateral prefrontal cortex 5-HTP derived activity, whereas PMD women displayed the opposite (p = 0.0001). Menstrual phase changes in this asymmetry (premenstrual—follicular) correlated with changes in self ratings of ‘irritability’ for the entire group (rs = -0.595, p = 0.006). The PMD group showed a strong inverse correlation between phase changes (premenstrual—follicular) in plasma levels of estradiol and phase changes in the laterality (dx/sin) of radiotracer activity in the dorsolateral prefrontal ROI (rs = -0.635; 0.027). The control group showed no such correlation. Conclusion Absence of increased premenstrual right-sided relative 5-HTP-derived activity of the dorsolateral prefrontal cortices was found to strongly correlate to premenstrual irritability. A causal relationship here seems plausible, and the findings give further support to an underlying frontal brain disturbance in hormonally influenced serotonergic activity in women with PMD. Because of the small number of subjects in the study, these results should be considered preliminary, requiring verification in larger studies.